COVID-19: Large-scale collective action, government intervention, and the importance of trust - Harring, Niklas; Jagers, Sverker C.; Löfgren, Åsa (World development, 2021)
•Country variations in COVID-19 policy interventions are understood by applying collective action theory.•Through comparison with other large-scale collective action problems, insights on COVID-19 policies are gained.•Reciprocal trust is a relevant factor when analyzing policy responses to the pandemic worldwide. In this article we apply a large-scale collective action framework on the spread of the COVID-19 virus. We compare the pandemic with other large-scale collective action problems – such as climate change, antimicrobial resistance and biodiversity loss – which are identified by the number of actors involved (the more actors, the larger the scale); the problem’s complexity; and the spatial and temporal distance between the actors causing and being affected by the problem. The greater the extent of these characteristics, the larger the scale of the collective action problem and the smaller the probability of spontaneous collective action. We argue that by unpacking the social dilemma logic underlying the spread of the COVID-19 virus, we can better understand the great variation in policy responses worldwide, e.g., why some countries are adopting harsher policies and enforcing them, while others tend to rely more on recommendations. We claim that one key factor is trust and, more precisely, reciprocal trust, both horizontally among people and also vertically between people and their governments – and vice versa. Citizens must trust that the recommendations they receive from the public authorities are correct, that these are in their (or the collective’s) best interest, and that most others will follow the recommendations. Simultaneously, government authorities must trust that their citizens will transform the recommendations into collective action. When this situation is present, we argue that governments enjoy a large degree of collective action capital, which potentially open up for a wider palette of policy options.